Influência da temperatura de armazenamento na qualidade das inflorescências de estrelítzia (strelitzia reginae banks ex aiton) - Silva Vieira, Marcos Ribeiro da; Pereira Lima, Giuseppina Pace [UNESP]; Souza, Angela Vacaro de [UNESP]; Oliveira, Nelson Geraldo de; Simoes, Adriano do Nascimento (Univ Federal Uberlandia, 2014)
This work was based to study the influence of the storage temperature (cold and room temperature) in the quality of inflorescences strelitzia. The scapes were selected, labeled and there were zero problems concerning mechanical damage, disease and/or plagues. Subsequently this period, the scapes were moved randomly to recipients with water, in which two postharvest trials were conducted. In experiment 1, the flower scapes were placed in buckets with water from public supply and sanitation department and taken to a cold room at temperature of 7.5 degrees C and RH of 90%, for a twelve day period. For the experiment 2, were kept under the same conditions but at room temperature for a period of six days. In both experiments, the visual analysis: color, gloss, stains (by assigning notes), opening and drop florets (count) were evaluated at intervals of four days in cold and every 48 hours at ambient temperature conditions. In both experiments, the visual analysis: color, gloss, stains (by assigning notes), opening and drop florets (count) were evaluated at intervals of four days in cold and every 48 hours at ambient temperature conditions. The sepal is the organ that showed greater loss in coloration. The variable gloss showed the same pattern for the two experiments. Incidences of stains on the inflorescences occurred in patches at room temperature. The scapes increased number of florets open in cold. This tendency did not occur at room temperature. No were observed differences in the fall of florets. Conclude that the storage temperature does not contribute to postharvest quality of strelitzia.

O presente trabalho tem por objetivo de estudar a influência da temperatura de armazenamento (câmara fria e temperatura ambiente) na qualidade das inflorescências de estrelítzia. Escapos florais foram selecionados, etiquetados e descartados quanto à presença de danos mecânicos, doenças e/ou pragas. Transcorrido esse período, foram transferidos para recipientes, onde foram submetidos a dois experimentos. No experimento 1, escapos foram colocados em baldes contendo água da rede pública e levadas para câmara fria a 7,5 ºC e UR de 90%, por um período de doze dias. No experimento 2, os escapos foram mantidos nas mesmas condições, porém em temperatura ambiente por um período de seis dias. Nos dois experimentos, as análises visuais: coloração, brilho, manchas (através da atribuição de notas), abertura e queda de floretes (contagem) foram avaliadas em intervalo de quatro dias em câmara fria e a cada 48 horas em condições de temperatura ambiente. A sépala foi o órgão que apresentou maior perda na coloração. A variável brilho apresentou o mesmo comportamento em relação aos dois experimentos. Maiores incidências de manchas nas inflorescências ocorreram em temperatura ambiente. Os escapos apresentaram aumento no número de floretes abertos em câmara fria. Essa tendência não ocorreu em temperatura ambiente. Não foram observados diferenças na queda de floretes. Conclui-se que a temperatura de armazenamento não contribui para a qualidade pós-colheita de estrelítzia.
Influence of storage temperature on quality of inflorescences strelitzia (strelitzia reginae banks ex aiton)
Keywords: Strelitzia reginae; Flowers; Conservation; Senescence; Strelitzia reginae; Flores; Conservação; Senescência